Efektivitas Penerapan Model Pembelajaran Student Facilitator and Explaining terhadap Kemampuan Representasi Matematis Siswa - Yuliany, Nur; Majid, Ahmad Farham; Asima, Nurul; Sulasteri, Sri; Abrar, Andi Ika Prasasti (Faculty of Tarbiyah and Teacher Training, 2024)
This research aims to evaluate the impact of using the Student Facilitator and Explaining learning model on students' mathematical representation abilities. This research uses a quantitative approach with a Quasi-Experimental Design research design with a design form, namely a non-equivalent control group design. The sample chosen was 56 students from a population of 111 students at SMA Negeri 11 Bulukumba, using a simple random sampling technique. Data was collected using tests to assess mathematical representation abilities, observations to determine the implementation of learning scenarios and questionnaires. The data obtained were analyzed using descriptive statistical tests and inferential statistical tests. The research results show differences in the mathematical representation abilities of students who use the Student Facilitator and Explaining model with students who are taught using direct learning. The Student Facilitator and Explaining Learning Model effectively improves the mathematical representation abilities of class XI MIPA students at SMA Negeri 11 Bulukumba.